Water absorption effect on electrical resistivity of kaolinite-superabsorbent polymer mixture - Nor Shafinas, Shafiee (2019)
A research on the Kaolinite – Superabsorbent Polymer (SAP) mixture, which is a type of clay that dominated in Malaysia. The main high quality kaolin deposits in peninsular Malaysia that is found near Bidor and Tapah, Perak. This kaolinite clay soil used as an alternative material to replace bentonite in grounding system. The study was conducted to establish Soil Water Retention Curve (SWRC) and to determine the resistivity behaviour of the Kaolinite – SAP. The investigation on the corrosion of earthing electrode also has been considered in this study. The research focuses only on laboratory tests under Vapour Equilibrium Technique (VET), Wenner Four – Point test and mass – loss method for corrosion investigation. This study showed the water retention curve (WRC) for Kaolinite – SAP mixture. The addition of SAP increased the water retention behaviour of Speswhite, FMC and S300 kaolin. Kaolin without SAP has a high resistivity at its dry states. However, the resistivity decreases abruptly with increasing water content. Kaolin with SAP also has the same situation where resistivity is high at its dry states and get decrease with the water content is increase. Experimental result from the mass – loss method showed that the copper electrode corrosion rates for kaolin with SAP mixture are greater than kaolin without SAP. Water is one of the factors that affect soil corrosion.